Building Entrepreneurship Capacity of Adult Learners While Converting Literacy Education to Functional Literacy: A Case Study of Lift Above Poverty Alleviation Programme in Ibadan Metropolis, Nigeria - Quadri, Ganiyu Oluwaseyi; Muibi, Taofeek Gbolahan; I. Ukpere, Wilfred (Journal of Ecohumanism, 2025)
The research examined the impact of microfinance intervention, specifically business and farming loans, on the quality of life of beneficiaries of the Lift Above Poverty Alleviation Programme in Ibadan Metropolis. Utilising a descriptive survey research design, the study included all programme beneficiaries, with a sample size of 200 individuals randomly chosen from four branches of the LAPO bank, including Sango, UI, Ojoo, and Iyana Church. Data collection was done using a 30-item questionnaire measuring the Poverty Alleviation Programmes of Lift Above Poverty Organisation’(PAPLAPOS) Scale (r=.84), which consisted of two subs-scales: Business Loan Scale (r=.83) and Farming Loan Scale (r=.85). The data collected were analysis through the descriptive statistics involving frequency counts, simple percentages, multiple regression, as well as mean and standard deviation. The results of the research indicated that the impact of the microfinance intervention (specifically Business and Farming loans) on the quality of life of the beneficiaries was statistically significant (F (2,148) = 111.425; R2 = .568), explaining 64.3% of the variance. In light of these findings, it is suggested that there is a necessity for microfinance initiatives focusing on enhancing basic and functional literacy to foster the advancement of entrepreneurship, development, and adult education practices in Nigeria.